Sources of Food Affect Dietary Adequacy of Inuit Women of Childbearing Age in Arctic Canada - Schaefer, Sara E; Erber, Eva; Trzaskos, Janel P; Roache, Cindy; Osborne, Geraldine; Sharma, Sangita (Journal of Health, Population and Nutrition, 2011)
Dietary transition in the Arctic is associated with decreased quality of diet, which is of particular concern for women of childbearing age due to the potential impact of maternal nutrition status on the next generation. The study assessed dietary intake and adequacy among Inuit women of childbearing age living in three communities in Nunavut, Canada. A culturally-appropriate quantitative food-frequency questionnaire was administered to 106 Inuit women aged 19-44 years. Sources of key foods, energy and nutrient intakes were determined; dietary adequacy was determined by comparing nutrient intakes with recommendations. The prevalence of overweight/obesity was >70%, and many consumed inadequate dietary fibre, folate, calcium, potassium, magnesium, and vitamin A, D, E, and K. Non-nutrient-dense foods were primary sources of fat, carbohydrate and sugar intakes and contributed >30% of energy. Traditional foods accounted for 21% of energy and >50% of protein and iron intakes. Strategies to improve weight status and nutrient intake are needed among Inuit women in this important life stage. Key words: Arctic; Childbearing age; Cross-sectional studies; Diet; Dietary adequacy; Food consumption; Inuit; Maternal nutrition; Nutritional status; Canada DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8899 JHPN 2011; 29(5): 454-464